Online Da'wah Media Management Strategy in the Social Media Era: A Case Study of Dutaislam.or.id - Wahyu Khoiruz Zaman (IJoIS: Indonesian Journal of Islamic Studies, 2023)
The development of social media has changed the production, distribution, and consumption of Islamic messages in the digital public sphere. This transformation creates challenges for website-based online da'wah media because public attention increasingly shifts to social media platforms that are fast, visual, interactive, and algorithm-driven. This article analyzes the management strategy of Dutaislam.or.id as an online da'wah medium in responding to the social media era. This study uses a qualitative case study method based on digital observation of the Dutaislam.or.id website, documentation of selected rubrics and articles, examination of connected social media channels, and limited interviews with media managers. The findings show that Dutaislam.or.id does not abandon the website as the main basis of digital da'wah. The website is positioned as a center for content production, Islamic knowledge archives, and the strengthening of Ahlussunnah wal Jamaah narratives, while social media are used for distribution, amplification, interaction, and audience expansion. This strategy indicates that adaptation to the social media era does not always require full migration to social platforms, but can be carried out through the integration of websites as content centers and social media as distribution spaces.